3 - The ECOWAS Court and the Politics of Access to Justice in West Africa: Adewale Banjo - Banjo, Adewale (Africa Development, 2007)
Although the creation of the ECOWAS Community Court of Justice (ECJ) was approved in 1991 in pursuant to the provisions of Articles 6 and 15 of the 1993 Revised Treaty of the Economic Community of West African States, it was only set up a decade later in 2001. By utilising a content-analysis method, in addition to extensive personal interviews with the President of the Court, this study describes the emergence, composition, vision and competence/jurisdiction of the ECJ. The paper probes the various challenges currently faced by the ECJ, which include among others, logistics, limited public awareness among ECOWAS citizens, and non use by member states. The inability of ECOWAS citizens to access justice is given prominent emphasis with reference to the case of Afolabi Olajide vs. Federal Republic of Nigeria. The case typifies the extent to which the ECJ’s establishment fulfilled or failed to meet the expectation of ECOWAS citi- zens’ quest for justice. The study’s conclusion examines current efforts at broad- ening access to the court for citizens of the community.